Epithelioid trophoblastic tumor: Clinical presentation, diagnosis, and treatment - D. A. Lisayev; B. O. Toloknov; E. E. Makhova; I. V. Markina (Опухоли женской репродуктивной системы)
Epithelioid trophoblastic tumor (ETT) is a rare form of trophoblastic disease, which is characterized by high malignancy and a number of diagnostic features: a long interval between the last pregnancy and labor and the onset of the disease; a visual pattern at gynecological examination, relatively low β-chorionic gonadotropin (CG) levels, as well as the diffuse expression of cytokeratins-7 (+++) and -18 (+++), р63 (nuclear ++), E-cadherin (+++), EGFR (+), and CD-117(++) by tumor cells, as determined by immunohistochemical assay, and focal expression of CG (++) and PLAP (+) by these cells.